Implementasi Pelayanan Islami dalam Meningkatkan Citra Usaha Ayam Geprek Kejora La Vau Kitto di Kota Payakumbuh - Ulqiyanur Husnah; Era Sonita (ARZUSIN, 2026)
Although the implementation of Islamic service in culinary businesses has received attention in several studies, research that specifically discusses its application in improving business image in culinary micro, small, and medium enterprises (MSMEs) remains limited. This study aims to analyze and describe the implementation of Islamic service in improving the business image of Ayam Geprek Kejora La Vau Kitto in Payakumbuh City. This study employed a qualitative approach with a case study design involving 11 informants, consisting of 1 business owner, 3 employees, and 7 consumers selected through a purposive sampling technique. Data were collected through observation, in-depth interviews, and documentation, and were then analyzed using thematic analysis techniques through the stages of data reduction, data display, and conclusion drawing. The findings showed that the implementation of Islamic service had been carried out through the values of honesty, friendliness, responsibility, and justice in service, which contributed to increasing customer satisfaction and trust as well as forming a positive business image. However, the implementation of this service has not been fully consistent and is still influenced by other factors, such as price, facilities, and operational conditions. These findings contribute to the development of Islamic service theory in the context of sharia business and broaden understanding of the relationship between service quality and business image in culinary MSMEs. The conclusion of this study confirms the importance of consistency in implementing Islamic service to improve business image, and encourages business actors to strengthen service quality and operational management. The implications of this study include theoretical contributions to the development of the sharia business literature and practical implications for MSME actors, while also opening opportunities for further research on other factors influencing business image.